Positron emission tomography imaging of brain tumors - Wong, Terence Z; van der Westhuizen, Gert J; Coleman, R Edward (Neuroimaging clinics of North America, 2002)
A wide variety of metabolic features of brain tumors can be imaged using PET, including glucose metabolism, blood flow, oxygen consumption, amino acid metabolism, and lipid synthesis. Currently, FDG is the most widely available PET tracer for body imaging and brain imaging. Malignant brain tumors, like many other soft tissue tumors, show increased glucose metabolism, which is reflected on FDG-PET imaging. FDG-PET imaging of brain tumors provides information on tumor grade and prognosis. Compared with other organ systems, FDG-PET imaging of the brain presents unique challenges because of the high background glucose metabolism of normal gray matter structures. Coregistration of the MRI (or CT) and FDG-PET images is essential for accurate evaluation of brain tumors and is performed routinely at the authors' institution. The heterogeneous nature of gliomas can result in significant sampling errors when patients are biopsied for primary tumor diagnosis or recurrent disease. FDG-PET can be used to define the most metabolically active targets for stereotactic biopsy. This in turn can improve diagnostic accuracy and reduce the number of biopsy samples required. FDG-PET is also useful for evaluating residual or recurrent tumor following therapy, and can be used to survey patients with low-grade brain tumors for evidence of degeneration into high-grade malignancy. In the case of suspected tumor recurrence or progression, PET can aid in defining appropriate targets for biopsy. One limitation of FDG-PET is the occasional inability to distinguish radiation necrosis from recurrent high-grade tumor. A second limitation is that FDG-PET is less sensitive than contrast-enhanced MRI for detecting intracranial metastases, and it is the authors' experience that brain studies should not be included as part of routine whole-body PET studies. Other tracers, such as 11C-methionine and FCH, also avidly accumulate in brain tumors and have the advantage of low background cortical activity. The relationship between degree of uptake of these agents and tumor grade is not established. These tracers may be useful in specific clinical situations, however, such as tumor localization for treatment planning or evaluation of low-grade tumors.